Antioxidant, Antinociceptive and CNS Activities of Viscum orientale and High Sensitive Quantification of Bioactive Polyphenols by UPLC - Khatun, Amina; Rahman, Mahmudur; Rahman, Md. Mahfizur; Hossain, Hemayet; Jahan, Ismet A.; Nesa, Mst. Luthfun (Frontiers in Pharmacology, 2016)
Viscum orientale Willd. (Loranthaceae) has long been used in traditional medicine to treat pain, neuropharmacological disorders and various forms of tumor but not yet been reported. The aim of this study is to rationalize the traditional medicinal use of this plant by evaluating the methanol extract of V. orientale leaves (MEVOL) for anti-nociceptive, CNS depressant and antioxidant activities and to quantify the bioactive polyphenols present in this plant. Five polyphenolic compounds namely gallic acid, vanillic acid, caffeic acid, ellagic acid and quercetin (17.54, 8.99, 99.61, 4523.31 and 100.15 mg/100 g of dry weight, respectively) have been identified in MEVOL using Ultra Performance Liquid Chromatography. Qualitative antioxidant activity determined by Thin Layer Chromatography indicated the presence of antioxidants. In quantitative antioxidant test using 2,2-diphenyl 1-picrylhydrazyl, MEVOL exhibited strong free antioxidant activity in a dose dependant manner (IC50= 6.63 µg/ml) compared with ascorbic acid (IC50= 1.91 µg/ml) and butylatedhydroxyanisole (IC50= 2.27 µg/ml) controls. Total phenolic content determined using Folin Ciocaltu reagent was found to be 73.4 mg gallic acid equivalent/g of extract, while flavonoid content estimated using aluminium chloride colorimetric method was 170.7 mg quercetin equivalent/g of extract. Anti-nociceptive activity of MEVOL measured using acetic acid and formalin induced pain models in mice was significant (p<0.001). MEVOL showed 65.6 and 88.8% writhing inhibition at 300 and 500 mg/kg body weight respectively comparing with standard diclofenac-Na (75.2% inhibition) at 25 mg/kg body weight in acetic acid induced pain model. In formalin induced pain model, paw licking was inhibited 45.93 and 56.4% in early phase and 55.66 and 72.64% in late phase at 300 and 500 mg/kg body weight respectively, while diclofenac-Na inhibited 60.47 and 61.32% in early and late phase at 10 mg/kg body weight respectively. In neuropharmacological activity test, overall behavioral test significantly reinforced CNS depressant activity. Spontaneous motor activities were reduced (p<0.05) in both hole cross and open field tests compared with diazepam. Antioxidant activity of MEVOL is likely due to the phenolic and flavonoid compounds present within the leaf tissues. This study reveals significant in-vivo anti-nociceptive and CNS depressant activities which justifies traditional medicinal applications of V. orientale.